Adorno, Habermas, and the search for a rational society - Cook, Deborah, 1954- (Routledge studies in social and political thought ;, 2004)
Exploring the premises shared by both critical theorists, along with their profound disagreements about social conditions today, this book defends Adorno against Habermas' influential criticisms of his account of Western society.